Morpho-Agronomical and Nutritional Evaluation of Cultivated Einkorn Wheat (Triticum monococcum L. ssp. monococcum) Lines Sown in Autumn and Spring Seasons - Kefi, Servet; Kavuncu, Orhan; Bıyıklı, Engin; Salantur, Ayten; Alyamaç, Mehmet Emin; Kaplan Evlice, Asuman; Pehlivan, Aliye (Asian Online Journals, 2021)
Nowadays diploid einkorn wheat (Triticum monococcum L. ssp. monococcum), widely cultivated in the Neolithic age, has been reconsidered as the valuable genetic resource for breeding and organic farming due to its high resistance to pests and diseases, adaptation to harsh climates, ability to provide acceptable yields on poor soils even with low/without inputs and high nutritional values. In this research, local 45 cultivated einkorn lines, selected from 500 single rows planted by each single spikes collected from total 50 farmers’ fields in 34 villages of Kastamonu/Turkey, were evaluated in terms of their morpho-agronomical traits and nutritional characteristics during two sowing seasons, autumn 2017 and spring 2018. Einkorn lines sown in two different seasons showed significant variations for heading time, plant height, lodging susceptibility, spike length, number of spikelets per spike, gross grain yield, amount of glume, single kernel weight, kernel diameter, hardness index, grain protein content and the color (a, b, L) values of flour. Furthermore, most of the correlation coefficients between these characteristics were found to be significant. All lines showed “facultative” growth habit, flowering well when sown both in autumn and in spring. Although lines sown in autumn had more yields, the same lines sown in spring provided higher grain quality and more resistance to lodging due to having shorter stems. In order to enable sustainable future use of einkorn, further research is suggested for reduction of plant height to avoid lodging and improvement of grain yield to compete with modern high yielding wheat cultivars.
Keywords: 2. Zero hunger; 15. Life on land